Use of Guar Gum as a Clay-Flocculating Agent for Chalcopyrite Flotation - M. Jeldres; R. J. Jeldres; L. Gutierrez (International Mineral Processing Congress, 2018)
"Clays are present in a large number of mineral deposits and are commonly found as gangue. Its complex chemical structure, characterised by anisotropic surfaces, makes its presence a permanent challenge for flotation operations, increasing the reagent consumption, decreasing the quality of the concentrate, and changing the rheological properties of the system. In this context, the main objective of this research is to improve the floatability of chalcopyrite minerals in the presence of clays by using guar gum, a low molecular weight organic polymer, which acts as a surface coating agent for clays. Clay Minerals Society provided the kaolinite sample and the chalcopyrite sample was purified from mineralized rock specimens obtained from Ward’s Natural Science Establishment. Micro flotation tests were carried out in a 150 cm3 Partridge-Smith cell, using compressed air as the gas phase at a flow rate of 80 cm3/min. Potassium amyl xanthate (PAX) and methyl isobutyl carbinol (MIBC) were used as a collector and a frother, respectively. The results showed that the use of guar gum improves the recovery of chalcopyrite in the presence of kaolinite because it induces the formation of clay aggregates that settle by gravitational effects, preventing the 'coating effect' and decreasing excessive collector consumption. pH played a key role in the guar gum performance, which was most effective at highly alkaline conditions (pH 11), where the copper recovery improved from 73% to 90%. The work has significant implications for the mineral flotation in the presence of clay minerals.INTRODUCTION The mining industry is continuously confronted with challenges that alert the sustainability of the sector. There is little availability of water, the grade of the deposits are getting smaller, and the gangue is becoming more complex. Usually, clays are part of the gangue in numerous systems, including copper ore, porphyry, nickel, platinum, etc. (Senior & Thomas, 2005). The structure is mainly composed of layers of tetrahedral silica (T) and octahedral alumina (O) that join in certain proportions: 1: 1 (T-O) and 2: 1 (T-O-T) (Theng, 2012). Also, they expose two crystallographically different surfaces: the faces, which tend to be negatively charged, and the edges, which carry a charge that changes from positive to negative depending on the pH (Van Olphen, 1977). One of the most common clays in copper deposits is kaolinite, whose structure is composed of an octahedral sheet of gibbsite bound to a tetrahedral silica sheet in the ratio 1:1"